GOTONG ROYONG SEBAGAI BUDAYA BANGSA INDONESIA DITINJAU DARI TEORI NILAI (BASIC HUMAN VALUES THEORY) - Arief, Mayangsari Imelda; Yuwanto, Listyo (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
This study aims to look deeper into the culture of gotong royong. Gotong royong is an Indonesian culture. This culture is not just cleaning up something or building something but it contains a profound meaning about help and harmony in life. This culture is rooted in Indonesian society and becomes the identity of Indonesian people in which allows people to help each other to help and maintain harmony and group dynamics. In the education field, this culture carried out early when students working on group assignments and the study groups, also through the role of teachers who help intensely on students. This study uses the theoritical review method in previous research which discusses the role of gotong royong in maintaining harmony in community life in Indonesia. This research looks from the perspective of the basic human value theory developed by Shalom Schwartz. It can be concluded that the culture of gotong royong has universalism, security, tradition and stimulation values.